POLA PENCEGAHAN PENYEBARAN RADIKALISME ISLAM DI MEDIA SOSIAL : (Studi Kasus Reskrimsus POLDA NTB) - Yapa Yuhida (Jurnal Dakwah Tabligh, 2023)
The spread of a lot of information and news about radicalism on social media will be fatal for someone if they are unable to filter information that is a hoax. People will tend to assume that all information is true, affecting their understanding and behavior. This research aims to identify the pattern of the spread of Islamic radicalism on social media Facebook and YouTube and describe the pattern of prevention by the NTB Police Special Criminal Investigation. The research method used is a qualitative approach with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings show that in the spread of radicalism on social media, there are two types of media: closed and open, however, radicalism is more likely to use closed social media that can only be accessed by certain members. Prevention of radicalism involves three patterns: Pre-emptive (posting Indonesian love content), Preventive (providing information on the dangers of radicalism), and Repressive (collaboration with security agencies in the prosecution of radicalism).